Universal ethics : perspectives and proposals from Scandinavian scholars (Raoul Wallenberg Institute human rights library ;, 2002)
Questions on universal ethics are of utmost importance for peaceful relations between nations, cultures and religions. Are there common values or are all morals just expressions for various political, economic or religious interests? In this book scholars from different academic fields and with various views discuss questions that in different ways concern both the possibilities and risks of universal or common ethics. The book is divided into five parts; philosophical and ethical perspectives, human rights perspectives, universal ethics and religion, globalization and global governance, universal ethics and Nordic values. Scholars from such fields as philosophy, ethics, human rights, history, political science, sociology and theology are represented. All of the authors are active researchers at Scandinavian universities. This collection of articles is directed to professionals in various disciplines, but can also serve as an introduction to the subject of universal ethics.